Differences in access to water, sanitation, and hygiene facilities among residents of Korail Slum, Bangladesh, during normal vs. water-logging situations - Md Mostafizur Rahman; Virasakdi Chongsuvivatwong; Alan F. Geater; Md Shamim Hayder Talukdar; Wit Wichaidit (PLoS ONE, 2025)
Background Slum areas in Dhaka, Bangladesh, experience frequent water-logging after heavy rain. However, the extent to which access to water, sanitation, and hygiene (WASH) varies between normal vs. water-logging periods has not been described. The objectives of this study are: 1) to describe WASH access and behaviors among Korail Slum residents during normal vs. water-logging periods, and; 2) to describe the extent to which the differences in WASH access and behaviors between normal vs. water-logging periods varied by socioeconomic status (SES). Methods We conducted a cross-sectional study in Korail Slum, Dhaka, Bangladesh, during November 2024 using face-to-face interviews and rapid observation of WASH infrastructures. We selected adult residents to Korail Slum via systematic random sampling and invited them to participate. We interviewed participants regarding WASH access and behaviors, as well as their education, income, and asset ownership (i.e., socioeconomic status (SES) indicators). We categorized participants into SES tertiles using principal component analysis (PCA). We analyzed data using descriptive statistics and McNemar’s tests. Results Nearly all of our participants (n = 404) reported a Basic level of water access during normal and water-logging periods, and no participant reported using unimproved latrines or open defecation. Approximately 85% of the participants reported access to Basic hygiene facilities during normal periods, most (95%) of whom also reported the access during water-logging periods (p-value = 0.134). The majority of participants did not always wash their hands at key moments during the normal period. Among those who reported always washing hands during the normal period, between 15% to 30% regressed and did not always wash their hands during the water-logging period. There were no statistically significant variations in the difference between WASH access and behaviors at normal vs. water-logging periods by socioeconomic tertile. Conclusion We found near-universal access to water and improved sanitation, but low level of hand hygiene behaviors. Limitations regarding generalizability and potential social desirability bias should be considered as caveats in the interpretation of the study findings.